Frequency of Microsatellite Metastases, Satellite Metastases, and Residual Tumor in Thin Melanomas: A Retrospective Cohort Study - Wennberg, Ebba; Bittar, Rudy; Svensson, Helena; Paoli, John (Dermatology Practical & Conceptual, 2025)
Introduction: Thin invasive melanomas (Breslow thickness ≤1.0 mm) are increasing in incidence in Sweden, but also notably have a favorable prognosis. Treatment typically involves complete diagnostic excision followed by wide local excision (WLE) to eliminate potential microsatellite and satellite metastases, along with residual melanoma. Objectives: This study aimed to investigate the frequency of microsatellite and satellite metastases in diagnostic excision specimens and residual melanoma in WLE specimens from thin melanomas. Methods: This was a retrospective cohort study including consecutively collected primary thin melanomas excised at Sahlgrenska University Hospital between January 2014 and December 2020. Results: Among 1,012 cases, no microsatellites were observed in the diagnostic excisions. Meanwhile, macroscopic satellite metastases were only present in 0.2% of the cases (n=2). Among 887 melanomas undergoing WLE with available data (87.6%), no microsatellites or satellite metastases were found in the extra tissue removed. Of the completely excised melanomas (n=936, 92.5%), only 0.2% (n=2) exhibited residual melanoma in the WLE. Conclusions: Our findings align with previous studies suggesting that WLE may result in excessive and unnecessary treatment for completely excised thin melanomas. The requirement of performing WLEs following complete excision of thin melanomas needs to be reevaluated.